EFFECTS OF THE USE OF ELECTRONIC CALCULATOR ON OUTCOMES OF MATHEMATICS INSTRUCTION (1987)
The teaching - learning of mathematics in the primary and secondary schools is often characterized by algorithmic computations to the detriment of concept learning and problem-solving. Invariably pupils often become disinterested in the tedious mathematical computational chores. This study was therefore, set up to investigate the effects of the use of electronic calculators on the outcomes of mathematics instruction. The learning Outcomes investigated were achievement in mathematics and attitudes toward mathematics and calculators. A paradigm of 3 x 3 factorial design of three ability levels: high, average and low by treatment groups: two experimental groups - unrestricted calculator and restricted calculator groups, and a control group - the non-calculator groups were used. There were two stages of the study: Pilot and Main. The pilot study was carried out in only one school and lasted six weeks while the main study took place in three comparable schools and had a duration also of six weeks. The schools were mixed in all cases. These schools were selected by multi-stage random sampling from ninety-five Secondary schools in Ibadan municipality at the time. For the main study, 126 subjects selected from three schools completed the study. The following null hypothesis were treated at α=.05. There will be no significant difference in the achievement scores of pupils who use (i) calculators in instruction and tests (the unrestricted groups) (ii) calculators in tests only (restricted groups) and (iii) no-calculators at all groups. The null hypothesis one was rejected because there was significant difference in the mean post-tests cores of those groups who used calculators in instruction and tests, calculators on tests only groups, and non-calculators groups (F(2,123) =16.234, p<.031) (2) There will be no significant difference in the achievement scores of pupils of low, average and high mental abilities. The null hypothesis two was rejected because there was significant difference in the mean post scores of those groups of low, average and high mentalability levels (F(2,123) = 14.776, p < .001) (3) There will be no significant difference in the attitudes towards mathematics and calculators of pupils who use calculators in instruction and tests, (ii) calculators in tests only, and (iii) non-calculators at all. The null hypothesis three was not rejected in entirety because there was no significant difference in the post attitude scores of the groups who use calculators in instruction and tests, calculators in tests only groups and non-calculator groups (F(2,123) = 1.217, p > .05). (4) There will be no significant difference in attitude to 'wards mathematics and calculators scores of those groups of high, average and low mental abilities. The null hypothesis four was not rejected entirely because there was no significant difference in the mean post-attitude scores of those groups of high, average and low mental ability levels (F(2,123) = 2.147, p > .05). (5) There will be no significant relationship between the attitudes of pupils towards mathematics and calculator-use in mathematics. The null hypothesis five was not rejected because there was no significant relationship between pupils' attitudes towards mathematics and calculator-use (F(1, 124) = 1 .57, p > .05). (6) There will be no significant relationship in pupils' mathematics achievement scores and post-attitude scores. The null hypothesis six was rejected because there was significant relationship in the post-test scores of the groups and the post-attitude scores (F(1,124) = 4.84, p < .05). Generally, the results showed that there were attitudinal changes between pre- and post-attitudes among all the groups, and that the calculator groups performed better than the non-calculator groups. The results have also shown that pupils within the same ability levels who use calculators will perform better than those who do not use calculators. Most studies on the use of calculators including this one have not found calculators to have debilitating effects rather it has computational advantage and promotes high achievement gains in mathematics. Teachers and pupils in secondary schools should be encouraged to utilize the advantage of calculators in algorithmic computations, so as to reduce those computational chores which often led to loss of interest in learners. However, further research could be done into the effectiveness and efficiency of calculators in concept formation, and problem-solving in secondary schools. In addition, research could be done to find out its effects at primary school level in Nigeria.